Recommended practices for wind farm data collection and reliability assessment for O&M optimization. (October 2017) - Hahn, Berthold; Welte, Thomas; Faulstich, Stefan; Bangalore, Pramod; Boussion, Cyril; Harrison, Keith; Miguelanez-Martin, Emilio; O'Connor, Frank; Pettersson, Lasse; Soraghan, Conaill; Stock-Williams, Clym; Dalsgaard Sørensen, John; et al.
Abstract: The paper provides a brief overview of the aims and main results of IEA Wind Task 33. IEA Wind Task 33 was an expert working group with a focus on data collection and reliability assessment for O&M optimization of wind turbines. The working group started in 2012 and finalized the work in 2016. The complete results of IEA Wind Task 33 are described in the expert group report on recommended practices for "Wind farm data collection and reliability assessment for O&M optimization" which will be published by IEA Wind in 2017. This paper briefly presents the background of the work, the recommended process to identify necessary data, and appropriate taxonomies structuring and harmonizing the collected entries. Finally, the paper summarizes the key findings and recommendations from the IEA Wind Task 33 work.